2019
DOI: 10.1155/2019/8418760
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Deep Learning for Identifying Differentially Expressed (DE) Biomarkers

Abstract: As a large amount of genetic data are accumulated, an effective analytical method and a significant interpretation are required. Recently, various methods of machine learning have emerged to process genetic data. In addition, machine learning analysis tools using statistical models have been proposed. In this study, we propose adding an integrated layer to the deep learning structure, which would enable the effective analysis of genetic data and the discovery of significant biomarkers of diseases. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Traditional statistical approaches are not suitable for detecting gene interactions, especially when interactions appear between more than two genes, or when the data are high-dimensional, meaning the data have many attributes or independent variables ( McKinney et al, 2006 ; Lai et al, 2019 ). Machine learning approaches have been widely used to identify disease biomarkers ( Lim et al, 2019 ; Moni et al, 2019 ; Tabl et al, 2019 ; Sanchez and Mackenzie, 2020 ). Recently, Sanchez et al identified methylation biomarkers for leukemia by investigating PPI for differentially methylated genes (DMGs) and differentially expressed genes (DEGs) using machine learning approach ( Sanchez and Mackenzie, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional statistical approaches are not suitable for detecting gene interactions, especially when interactions appear between more than two genes, or when the data are high-dimensional, meaning the data have many attributes or independent variables ( McKinney et al, 2006 ; Lai et al, 2019 ). Machine learning approaches have been widely used to identify disease biomarkers ( Lim et al, 2019 ; Moni et al, 2019 ; Tabl et al, 2019 ; Sanchez and Mackenzie, 2020 ). Recently, Sanchez et al identified methylation biomarkers for leukemia by investigating PPI for differentially methylated genes (DMGs) and differentially expressed genes (DEGs) using machine learning approach ( Sanchez and Mackenzie, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors used the deep learning-based feature representation of tumor-infiltrating lymphocytes in the cancer of the breast based on histopathological imaging for improving the detection process. Several other studies used the DNN model for detecting the subtypes of cancer by combining several types of transcriptomics data on breast cancer using deep learning techniques [62] and Identifying Differentially Expressed (DE) Biomarkers [63].…”
Section: Rq1: What Are the Common Deep Learning Methods For Breast Ca...mentioning
confidence: 99%
“…Recent advances in bioinformatics technologies have allowed significant improvements in the discovery of pathogenic genes of cardiovascular diseases. A large amount of gene data has been accumulated, and sophisticated methods for analyzing data have become crucial to explain the causes of disease (15). In this study, we screened differentially expressed genes (DEGs) in response to the regulation of KDM5A.…”
Section: Introductionmentioning
confidence: 99%